Analysing economic costs of invasive alien species with the invacost r package. Issue 9 (15th July 2022) - Leroy, Boris; Kramer, Andrew M.; Vaissière, Anne‐Charlotte; Kourantidou, Melina; Courchamp, Franck; Diagne, Christophe
Abstract: The reported costs of invasive alien species from the global database InvaCost are heterogeneous and cover different spatio‐temporal scales. A standard procedure for aggregating invasive species cost estimates is necessary to ensure the repeatability and comparativeness of studies. We introduce here the invacost r package, an open‐source software designed to query and analyse the InvaCost database. We illustrate this package and its framework with cost data associated with invasive alien invertebrates. First, the invacost package provides updates of this dynamic database directly in the analytical environment R. Second, it helps understand the heterogeneous nature of monetary cost data for invasive species, processes to harmonize the data and the inherent biases associated with such data. Third, it readily provides complementary methods to investigate the costs of invasive species at different scales, all the while accounting for econometric statistical issues. This tool will be useful for scientists working on invasive alien species, by (a) facilitating access to and use of this multi‐disciplinary data resource and (b) providing a standard procedure which will facilitate reproducibility and comparability among studies, one of the major critics of this topic until now. It should facilitate further interdisciplinary works including economists and invasion ecology researchers.